Effectiveness of Problem‐Based Learning in Chinese Dental Education: A Meta‐Analysis. Issue 3 (1st March 2013) - Huang, Beilei; Zheng, Liwei; Li, Chunjie; Li, Li; Yu, Haiyang
Abstract : This article provides a critical overview of problem‐based learning (PBL) practice in dental education in China. Because the application of PBL has not been carried out on a large scale in Chinese dental education, this review was performed to investigate its effectiveness. Databases were searched for studies that met the inclusion criteria, with study identification and data extraction performed by two reviewers independently. Meta‐analysis was done with Revman 5.1. Eleven randomized controlled trials were included. The meta‐analysis found that PBL had a positive effect on gaining higher theoretical (SMD=0.88, 95% CI [0.46, 1.31], p<0.0001) and practical scores (SMD=1.48, 95% CI [0.95, 2.00], p<0.0001). However, the pooled result did not show any positive effect on gaining higher pass rates (RR=1.06, 95% CI [0.97, 1.16], p=0.21). This meta‐analysis suggests that the PBL pedagogy is considered superior to the traditional lecture‐based teaching in this setting. PBL methods could be an optional supplementary method of dental teaching models in China. However, Chinese dental schools should devise PBL curricula according to their own conditions. The effectiveness of PBL should be optimized maximally with all these limitations.